Interaction of Panax quinquefolius Saponin and Dual Antiplatelets on Vascular Endothelial Function in Rats with Acute Myocardial Infarction. (19th May 2015) - Wang, Baojun; Liu, Yue; Shang, Qinghua; Zhang, Qingxiang; Zhang, Lei; Liu, Jiangang; Shi, Dazhuo
Abstract : The objective of this study is to investigate the interaction of Panax quinquefolius saponin (PQS) and dual antiplatelets (aspirin and clopidogrel) on antiplatelet activity and vascular endothelial function in rats with acute myocardial infarction (AMI). Forty-eight male SD rats were randomly designed into sham group, model group, dual antiplatelet group, and PQS plus dual antiplatelet group. AMI rats were induced by ligation of left anterior descending coronary artery (LAD) and dual antiplatelet agents and additional PQS to dual antiplatelets were intragastrically administered for 28 days, respectively. The ventricular cavity area and cardiac transverse area ratio in PQS + dual antiplatelet group showed a decreased tendency. PAgT(%) decreased significantly in both dual antiplatelet group and PQS + dual antiplatelet group. TXB2 concentration significantly decreased in dual antiplatelet and PQS + dual antiplatelet groups, whereas 6-keto-PGF1 α concentration significantly increased in PQS + dual antiplatelet group. Rats in PQS + dual antiplatelet group demonstrated a significant decrease in plasma ET-1 concentration and an increase in serum NO concentration compared with dual antiplatelet group. The combination therapy of PQS and dual antiplatelets showed some beneficial effects on vascular endothelial function and ventricular remodeling in rats with AMI.